Preparation method and application of ALD modified nano microstructure film

The ALD-modified nano-microstructure thin films address the performance limitations of TENGs by forming robust and efficient thin films on PTFE surfaces, enhancing output and durability through magnetron sputtering and ICP etching, effectively addressing material and structural issues in TENGs.

CN119685774APending Publication Date: 2025-03-25NANJING UNIV OF POSTS & TELECOMM
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411882036.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Current methods to enhance the performance of friction-based electrostatic generators (TENGs) face challenges such as increased material costs, reduced mechanical response due to thickness additions, and short-lived micro-nanostructures on soft materials, as well as inefficiencies in output for hetero-structured TENGs due to introduced bias effects.

Method used

The development of ALD-modified nano-microstructure thin films using a method involving magnetron sputtering for Ag layers, ICP etching for nano-column formation, and alternating deposition of Al2(CH3)3 and H2O to create AlOx layers on PTFE surfaces, forming robust and efficient thin films that maintain charge distribution and reduce polarization fields.

Benefits of technology

This approach enhances TENG performance by maintaining charge distribution and reducing polarization fields, while balancing cost, stability, and efficiency, leading to improved output performance and extended durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685774A_ABST
    Figure CN119685774A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of microstructures, and discloses a preparation method and application of an ALD modified nano microstructure film, and the method comprises the following steps: adopting a magnetron sputtering method to form an Ag atomic layer on the surface of a PTFE film as an etching mask plate; blowing plasma over the surface of the mask plate by adopting an ICP reactive ion etching method to form a nanorod morphology; a first precursor Al2 (CH3) 3 and a second precursor H2O are alternately used, chemical adsorption and reaction are carried out on the surface of the obtained PTFE, an AlOx insulating layer is formed, the range of x is 1-2, and finally the ALD modified nanometer microstructure film is obtained. The film prepared through the method has a microstructure, distribution of electrons at the tip of the microstructure enables the effective area of charges on the same plane to be reduced, and the performance of the ALD modified nanometer microstructure film is improved. The relative polarization field intensity is reduced, and the performance of the friction nanometer generator is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of microstructures, and in particular relates to a preparation method and application of an ALD modified nano-microstructure film. Background Art

[0002] Triboelectric nanogenerator (TENG) is a technology that converts mechanical energy into electrical energy. It has the advantages of simple design, high output power and low cost. The basic working modes of TENG include vertical contact separation, in-plane contact sliding, single electrode and independent triboelectric layer. Among the various working modes, contact separation is the main working mode. Its structure is mainly composed of two different dielectric materials and electrodes located at the top and bottom of the device. The physical contact between the two dielectric layers will produce charge transfer. When the materials begin to separate from the close contact state, the interfacial charge neutralization effect decreases with the increase of the electrode distance, resulting in an increase in the potential difference between the electrodes. This electric field change induces Maxwell displacement current, which makes the electron flow have a closed loop while the electrons flow from the negative electrode to the positive electrode through the external circuit, thereby realizing the power supply function of TENG.

[0003] Since contact electrification will produce a negative charge layer on the surface of the negative friction material, an electron concentration gradient will be formed from the surface to the inside of the material, thereby generating an electric field of a certain intensity on the top surface of the dielectric, inducing dielectric polarization and generating positive charge at the dielectric-electrode interface. Therefore, positive charge will be generated at the contact interface between the dielectric layer and the bottom metal electrode, resulting in a decrease in the net charge difference between the conductor pole and the dielectric pole, thereby causing the output efficiency to deteriorate.

[0004] From the perspective of contact electrification material properties, Maxwell equations and dielectric polarization, for negative friction layer materials, improving the electronegativity and insulation of materials can perfectly solve this problem. However, current materials science has encountered bottlenecks in this regard. In order to solve this problem, traditional methods often choose physical surface modification methods to enhance output; the first type is the modification of the dielectric-electrode interface: 1. Thickening the dielectric thickness to enhance insulation, thereby reducing the field strength; 2. Pasting the dielectric layer, taking into account the high electronegativity and film insulation of the friction material; the second type is the modification of the dielectric surface, that is, introducing means to enhance contact electrification at the conductor-dielectric interface, manufacturing microstructures on the dielectric surface, introducing the needle tip effect, and inducing more efficient migration of electrons. At the same time, some researchers introduced a polarization layer made of high dielectric constant material between the negative friction material and the bottom electrode, and used the self-polarization effect to enhance the polarization effect of the composite film, thereby introducing a bias effect in the TENG with the same dielectric material and enhancing the output of such TENG.

[0005] However, the above methods all have related defects. For the first type of physical surface modification, increasing the thickness or adding materials will lead to an increase in material costs and a decrease in device stability. At the same time, for soft materials, the increase in thickness will introduce a mechanical damping coefficient, which will attenuate the external physical response and also cause performance loss; for the second type of physical surface modification, the micro-nano structure constructed on the surface of the soft dielectric material will be completely lost due to external forces in the first hundred working cycles; and for the method of introducing a dielectric constant layer, the introduced bias effect is only applicable to TENGs of the same dielectric pole type. For conductor-dielectric TENGs, this type of bias is a negative bias that weakens the output efficiency.

[0006] Therefore, a physical surface modification method is urgently needed to obtain micro-nanostructured films to enhance the performance of friction generators. Summary of the invention

[0007] The purpose of the present invention is to solve the deficiencies in the prior art and to provide a preparation method and application of an ALD modified nano-microstructure film to enhance the performance of a friction generator.

[0008] In order to achieve the above object, the present invention is achieved through the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing an ALD modified nano-microstructure film, the method comprising the following steps:

[0010] Step S1, using magnetron sputtering to form a Ag atomic layer on the surface of the PTFE film as an etching mask;

[0011] Step S2, using ICP reactive ion etching to blow plasma across the surface of the mask plate to form a nanocolumn morphology;

[0012] Step S3, alternately using the first precursor Al2(CH3)3 and the second precursor H2O, chemically adsorbing and reacting on the surface of the PTFE obtained in step S2 to form an AlOx insulating layer, where x ranges from 1 to 2, and finally obtaining an ALD modified nano-microstructure film.

[0013] Preferably, in step S1, a magnetron sputtering method is used to form an Ag atomic layer on the surface of the PTFE film, specifically, the pressure of the chamber before the reaction is controlled to be 5e -4 Pa, the chamber temperature was 25 °C, an excitation current of 0.2 A and a bias voltage of 380 V were used, Ar gas was introduced into the chamber at a rate of 25 sccm, and sputtered on the surface of the PTFE film for 20 s, and finally a 5 nm thick Ag atomic layer was formed on the surface of the PTFE film.

[0014] Preferably, in step S2, ICP reactive ion etching is used to blow plasma across the surface of the mask plate to form a nanocolumn morphology, specifically: Ar, O2 and CBrF3 gases are used, wherein Ar, O2 and CBrF3 gases enter the reaction chamber at flow rates of 15.0, 10.0 and 30.0 sccm, respectively, and a plasma excitation source excites the Ar, O2 and CBrF3 mixed gas into plasma with an excitation power of 400 W, and etches the mask plate surface for 30 seconds to obtain a nanocolumn morphology with a depth of 10-100 nm.

[0015] Preferably, step S3 is specifically as follows: at 180°C, the first precursor Al2(CH3)3 is introduced into the reaction chamber at a rate of 15sccm to react with the OH groups adsorbed on the surface of PTFE to produce an oxygen-methylaluminum molecular layer and CH4 on the surface of PTFE, and the reaction time is 0.2s. Then, N2 is introduced at a rate of 15sccm to purge and remove the remaining Al2(CH3)3 and CH4, and the purge time is 15s. The second precursor H2O reacts with the oxygen-methylaluminum molecular layer on the surface of PTFE to remove all methyl ligands to form an AlOx insulating layer, and the reaction time is 0.2s. N2 is introduced again at a rate of 15sccm to purge the remaining H2O and CH4, and the purge time is 15s. The first precursor Al2(CH3)3 and the second precursor H2O are used alternately to finally obtain an ALD modified nano-microstructure film.

[0016] Preferably, the number of alternations is 45-500 times, and the thickness of the AlOx insulating layer is 5-60 nm.

[0017] Preferably, the thickness of the PTFE film in step S1 is 30 μm.

[0018] In a second aspect, the present invention provides an application of an ALD modified nano-microstructure film in a friction nano-power generation self-driven sensor.

[0019] The present invention has the following beneficial effects: the film prepared by the present invention has a microstructure, and the distribution of electrons at the tip of the microstructure reduces the effective area of ​​charges on the same plane, thereby reducing the relative polarization field strength; atomically deposited rigid dielectrics restore the microstructure to its original rigidity, thereby reducing the physical changes of the microstructure when subjected to external forces, maintaining the charge distribution density, and solving the problem of performance loss caused by changes in the dielectric constant; the method simultaneously takes into account multi-dimensional characteristics including cost, performance and stability, and the prepared film can enhance the performance of the friction nanogenerator. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The microstructure of the ALD modified nano-microstructure film prepared by the present invention is a top view;

[0021] Figure 2The microstructure of the ALD modified nano-microstructure film prepared by the present invention is a side view;

[0022] Figure 3 The surface element content of the ALD-modified nano-microstructure film prepared in the present invention (a is F, b is O, c is Al, and d is C);

[0023] Figure 4 Element content on the surface of untreated PTFE film (F in a, O in b, Al in c, and C in d);

[0024] Figure 5 The surface charge transfer comparison data of the ALD modified nano-microstructure film prepared by the present invention and the original PTFE film;

[0025] Figure 6 Comparison data of open circuit output voltage on the surface of the ALD modified nano-microstructure film prepared by the present invention and the original PTFE film;

[0026] Figure 7 The short-circuit output current comparison data of the ALD modified nano-microstructure film prepared by the present invention and the original PTFE film surface;

[0027] Figure 8 This is the loss test data of the ALD modified nano-microstructure film prepared in Example 2 after 10,000 cycles of testing. DETAILED DESCRIPTION

[0028] The technical scheme of the present invention is further illustrated by specific examples below, but the protection scope of the present invention is not limited thereto. The experimental methods in the following examples are conventional methods unless otherwise specified. The test materials used in the following examples are purchased from conventional biochemical reagent stores unless otherwise specified.

[0029] Example 1

[0030] A method for preparing an ALD modified nanostructured film comprises the following steps:

[0031] Step S1, using the uneven distribution of the atomic layer deposited by magnetron sputtering at a long target distance, the silver atoms spontaneously form an irregular, uneven and undulating microscopic mask on the surface of the PTFE film. First, the PTFE film is cut into 50mm*50mm size, and the four corners are glued and fixed on the circular range where the reference substrate and the target normal intersect; the mechanical pump and molecular pump are used to control the cavity pressure at 5e- 4Pa to ensure the purity of the sputtering excitation atmosphere; using an excitation current of 0.2A and a bias voltage of 380V, Ar gas is introduced into the cavity at a rate of 25sccm to conduct magnetronized argon ion bombardment on the target to sputter Ag atoms; finally, at a pressure of 0.6Pa and 25°C, a Ag atomic layer with an average thickness of 5nm is sputtered and deposited on the PTFE film, which is used as an etching mask to control the etching morphology.

[0032] Step S2, firstly, the four corners of the film obtained in step S1 are pasted to the center of the substrate; the chamber pressure is controlled at 6.7e by using a mechanical pump and a molecular pump. -5 Pa to ensure the purity of the etching atmosphere; adjust the excitation source power to 400W, and introduce Ar, O2 and CBrF3 gases into the reaction chamber at flow rates of 15.0, 10.0 and 30.0sccm respectively. After etching for 30s, a nanocolumn morphology with an average depth of 10-100nm is finally formed on the surface of the film.

[0033] Step S3, using the first precursor Al2(CH3)3 (trimethylaluminum, TMA) and the second precursor H2O to deposit an Al2O3 insulating layer on the surface of the film. First, the chamber is heated to 180°C, and the first precursor TMA is introduced into the reaction chamber at a rate of 15sccm. TMA reacts with the OH groups adsorbed on the surface of the film to produce an oxygen-methylaluminum molecular layer and CH4 on the surface of PTFE, and the reaction lasts for 0.2s; then, N2 is used to purge and remove the remaining Al2(CH3)3 and CH4 at a rate of 15sccm, and the purge time is 15s; then the second precursor H2O is introduced into the reaction chamber at a rate of 15sccm, and H2O reacts with the oxygen-methylaluminum molecular layer on the surface of PTFE to remove all methyl ligands; after the second reaction is completed, N2 is used again for 15s to purge and remove the remaining H2O and CH4. The above steps were repeated 45 times to form a 5 nm thick Al2O3 insulating layer on the PTFE surface, and finally an ALD modified nano-microstructure film was obtained.

[0034] Example 2

[0035] The difference from the embodiment is that the first precursor Al2(CH3)3 (trimethylaluminum, TMA) and the second precursor H2O are alternated 90 times to form an Al2O3 insulating layer with a thickness of 10 nm on the PTFE surface.

[0036] Example 3

[0037] The difference from the embodiment is that the first precursor Al2(CH3)3 (trimethylaluminum, TMA) and the second precursor H2O are alternated 500 times to form an Al2O3 insulating layer with a thickness of 60 nm on the PTFE surface.

[0038] The preparation method of the test device of the present invention is as follows: 1. Select two acrylic sheets with a length of 30 mm, a width of 30 mm, and a height of 8 mm as the substrates for carrying the positive and negative electrodes of the friction nano-power generation device; 2. Paste an aluminum foil film of the same size on one side of the acrylic sheet with a size of 30 mm*30 mm, and paste a wire to connect it to the test instrument; 3. Select one of the sheets as the negative electrode, and paste the side of the dielectric film with a microstructure insulating layer on the side with the aluminum foil through a layer of polyimide (PI) double-sided tape;

[0039] The test device parameters of this design are as follows: 1. The thickness of the PTFE film is 30μm; 2. The depth scale of the PTFE surface microstructure is 10-100nm; 3. The thickness of the Al2O3 insulating layer is 10nm; 4. The effective contact area of ​​the electrode is 30mm*30mm.

[0040] The test conditions are as follows: 1. The positive electrode is pasted with aluminum foil on one side and the negative electrode is pasted with dielectric film on the other side, and the distance between them is 10mm; 2. The acceleration of the electrodes moving towards each other is 500mm / s 2 ; 3. The interval between the electrode movement cycles is 20ms; 4. The electrodes are completely overlapped when in contact 5. The test uses the ABB MicroFlex e190 servo motor system to control the motors to run in opposite directions; 6. The test uses the Keithley 6514 electrometer to measure the transfer charge, open circuit output and short circuit output values. Compared with the original material, the net transfer charge peak of the TENG device prepared by the method proposed in the present invention is increased from 32nC to 45nC, which is 1.4 times the original parameter; the open circuit output voltage peak is increased from 140V to 180V, which is 1.28 times the original parameter; the short circuit current is increased from 7.75μA to 13.25μA, which is 1.71 times the original parameter.

[0041] The present invention effectively improves the output efficiency of the conductor-dielectric TENG. It can be widely used in self-driven sensors such as self-driven precision human body sensors. The emergence of this insulation method effectively reduces the thickness cost when the output efficiency of the sensor device is expected to be improved.

[0042] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the patent scope of the present invention.

Claims

1. A method for preparing an ALD modified nanostructured film, characterized in that: The method comprises the following steps: Step S1, using magnetron sputtering to form a Ag atomic layer on the surface of the PTFE film as an etching mask; Step S2, using ICP reactive ion etching to blow plasma across the surface of the mask plate to form a nanocolumn morphology; Step S3, alternately using the first precursor Al2(CH3)3 and the second precursor H2O to chemically adsorb and react on the surface of the PTFE obtained in step S2 to form AlO x Insulating layer, x ranges from 1 to 2, and finally an ALD modified nano-microstructure film is obtained.

2. The method for preparing the ALD modified nano-microstructure film according to claim 1, characterized in that: Step S1 uses magnetron sputtering to form an Ag atomic layer on the surface of the PTFE film, specifically: the pressure of the chamber before the reaction is controlled to be 5e -4 Pa, the chamber temperature was 25 °C, an excitation current of 0.2 A and a bias voltage of 380 V were used, Ar gas was introduced into the chamber at a rate of 25 sccm, and sputtered on the surface of the PTFE film for 20 s, and finally a 5 nm thick Ag atomic layer was formed on the surface of the PTFE film.

3. The method for preparing the ALD modified nano-microstructure film according to claim 1, characterized in that: In step S2, ICP reactive ion etching is used to blow plasma across the surface of the mask plate to form a nanocolumn morphology. Specifically, Ar, O2 and CBrF3 gases are used, wherein Ar, O2 and CBrF3 gases enter the reaction chamber at flow rates of 15.0, 10.0 and 30.0 sccm, respectively, and a plasma excitation source excites the Ar, O2 and CBrF3 mixed gas into plasma with an excitation power of 400 W, and etches the mask plate surface for 30 seconds to obtain a nanocolumn morphology with a depth of 10-100 nm.

4. The method for preparing the ALD modified nano-microstructure film according to claim 1, characterized in that: Step S3 is specifically as follows: at 180°C, the first precursor Al2(CH3)3 is introduced into the reaction chamber at a rate of 15sccm to react with the OH groups adsorbed on the surface of PTFE to generate an oxygen-methylaluminum molecular layer and CH4 on the surface of PTFE. The reaction time is 0.2s. Then, N2 is introduced at a rate of 15sccm to purge and remove the remaining Al2(CH3)3 and CH4. The purge time is 15s. The second precursor H2O reacts with the oxygen-methylaluminum molecular layer on the surface of PTFE to remove all methyl ligands to form AlO x Insulating layer, the reaction time is 0.2s, and N2 is introduced again at a rate of 15sccm to purge the remaining H2O and CH4. The purge time is 15s. The first precursor Al2(CH3)3 and the second precursor H2O are used alternately to finally obtain the ALD modified nano-microstructure film.

5. The method for preparing the ALD modified nano-microstructure film according to claim 4, characterized in that: The number of alternations is 45-500 times, AlO x The thickness of the insulating layer is 5-60 nm.

6. The method for preparing an ALD modified nano-microstructure film according to claim 1, characterized in that: The thickness of the PTFE film in step S1 is 30 μm.

7. Application of an ALD modified nanostructured film in a triboelectric nanopower generation self-driven sensor, characterized in that: The ALD modified nano-microstructure film is prepared by the method according to any one of claims 1 to 6.

Citation Information

Cited By

  • Ultra-thin asymmetric double-structure triboelectric flexible sensor with wide linear range and low detection limit and preparation method of ultra-thin asymmetric double-structure triboelectric flexible sensor

    CN120445477A